NOTE DE CURS LA DISCIPLINA OBICEIURI POPULARE ROMÂNEŞTI: OBICEIUL DRĂGAICA-SÂNZIENELE - USM ADMIN (Moldova State University, 2010)
The article contains less known, but important data about the custom of Drăgaica, as part of the calendar customs' cycle, from the season spring-summer. Even though this custom is not any more practiced in Moldova, there are many ethnographic and mythological dates preserved, linked with the circulation of this custom in different ethnographical Romanian zones, including the area between Nistru and Prut rivers.